Relationship between psychiatric disorders and criminal behaviour [Psi̇ki̇yatri̇k bozukluklarin suç davranişi i̇le i̇li̇şki̇si̇] - (:unkn) unknown (My University, 2010)
There is a common fear in the societies that patients with with psychiatric disorders have higher risk of commiting violent acts1. This fact has led to conducting number of scientific researches on investigating the relationship between criminal behaviour and psychiatric disorders in different countries. Papers in literature state that the rate of criminal behaviour among psychiatric patients is greater than normal population and the most common disorders leading to criminal behaviour are psychotic disorders, personality disorders, alcohol/substance abuse and childhood psychiatric disorders. However, it would be a wrong approach to label and stigmatize all the people with mental disorders as "dangereous, potentially criminal, liable to commit a violent act etc." The main subject to be discussed while debating on the rate of crime among psychiatric patients should be the reason why it is greater than the normal population. Researches indicate the insufficiency and the ineffectiveness of treatments as the main reason rather than having a disorder alone. Several methods need to be considered important in order to make treatments sufficient and effective. Dividing patients into subgroups according to their comorbidities, correct identification of etiologies, controlling alcohol/ substance use, systematic continuation of treatment, providing rehabilitation outside the institutions and achievement of social functioning would make an impact on reducing the rate of criminal behaviours commited by people with psychiatric disorders to the incidence found in normal population.